2005
DOI: 10.1007/s00254-004-1203-0
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall duration and debris-flow initiated studies for real-time monitoring

Abstract: A rainfall-induced debris flow warning is implemented employing real-time rain gauge The pre-warning for the time of landslide triggering derives the threshold or critical rainfall from historical events involving regional rainfall patterns and geological conditions. In cases of debris flow, the time taken cumulative runoff, yield abundant water for debris triggering, is an important index needs monitoring. In gathered historical cases, rainfall time history data from the nearest rain gauge stations to debris-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
62
3
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 157 publications
(72 citation statements)
references
References 9 publications
1
62
3
6
Order By: Relevance
“…The later study utilized data from 61 debris flows between 1989 and 2001, obtained from newspapers and interviews with local residents, and the I-D threshold was determined visually rather than statistically. The differences in threshold line slope between our study and Chien- Yuan et al (2005) are likely attributable to their relatively small sample size and subjective method for establishing I-D thresholds. Comparatively, we determined the I-D threshold using 107 debris flow events and employed statistical methods to ensure the validity of our results.…”
Section: Rainfall Conditions and I-d Thresholdsmentioning
confidence: 96%
See 4 more Smart Citations
“…The later study utilized data from 61 debris flows between 1989 and 2001, obtained from newspapers and interviews with local residents, and the I-D threshold was determined visually rather than statistically. The differences in threshold line slope between our study and Chien- Yuan et al (2005) are likely attributable to their relatively small sample size and subjective method for establishing I-D thresholds. Comparatively, we determined the I-D threshold using 107 debris flow events and employed statistical methods to ensure the validity of our results.…”
Section: Rainfall Conditions and I-d Thresholdsmentioning
confidence: 96%
“…Therefore, it is difficult to predict the exact time of a mass movement using only I-D thresholds. Many studies have found that peak rainfall intensity occurs very close to the time of mass movement occurrence (Aleotti 2004;Chien-Yuan et al 2005;Guzzetti et al 2007Guzzetti et al , 2008Dahal and Hasegawa 2008;Saito et al 2010aSaito et al , 2010b. Thus, analyzing peak rainfall intensity in conjunction with I-D thresholds is useful for characterizing mass movements.…”
Section: Rainfall Conditions and I-d Thresholdsmentioning
confidence: 99%
See 3 more Smart Citations